Effect of structure on the secondary electron emission of tetrahedral amorphous carbon films. (February 2020) - Kang, Yongfeng; Li, Bin; Zhao, Jingyi; Ge, Bangzhi; Weng, Ming; Shi, Zhongqi; Zhao, Yuqing
Abstract: Tetrahedral amorphous carbon (ta-C) films are appealing for electronic device due to its unique electronic and optical properties. In this work, ta-C films were prepared by filtered cathodic vacuum arc (FCVA) method which is developed by adopting a focusing-deflection system for adjusting the ion beam current density and increasing the deposition field size. The surface morphology of ta-C films prepared by this developed FCVA was presented by scanning electron microscopy (SEM) and atomic force microscopy (AFM). The results reveal that the roughness of these ta-C films is only ∼0.4 nm and bias voltages almost unaffected to the surface morphology of the films. Moreover, secondary electron emission properties of ta-C films were investigated with various bias voltages. Compared with bare stainless steel substrate, the secondary electron yield (SEY) of ta-C films decreases significantly. Furthermore, the films deposited at the bias voltages in the range of 110–155 V possess the highest maximum secondary electron emission coefficient ( δ max ) compared to others, which matches well with the variation of sp 3 content in the films from Raman spectra analyses. These results indicate that the SEY can be tailored by the sp 3 /sp 2 ratio of ta-C films. Highlights: The relationship between SEY and sp 3 contents of ta-C films is revealed. A novel approach is proposed that the SEY of ta-C films can be adjusted conveniently by varying substrate bias voltages. The roughness of ta-C films achieves ∼0.4 nm and bias voltages almost unaffected to the surface morphology of the films.